Defacing the Female personhood: deconstructing vitriolage through a reading of Reshma Qureshi’s Being Reshma and Meghna Gulzar’s Chhapaak - Dahiya, Mahima; Rani, Rekha (Penerbit Universiti Kebangsaan Malaysia, 2024)
Our bodies act as sites of identity formation as well as association with the world. It is the primary way of establishing a connection with our surroundings. On the surface, skin serves as a protective layer of the body, but it also becomes an embodiment of the person's identity. An acid attack is an act of violence that completely damages this protective shield of the body. The paper addresses the issue of vitriolage- how it disfigures the face and mutilates the very being of a person. The violent physiological disfigurement, especially that of the face, as it is an important front to place and assert oneself in society, leads to a complete disruption of one’s socio-personal relationships. The critical study of texts undertaken is an attempt to understand the physical and psychological sufferings and resilience of the acid attack victim/survivor. As an extension of the psychological consequences of the experience, the victim starts comparing the human self with animalistic/monstrous tendencies. Facial disfigurement, in general, tends to arouse some affective response in public, ranging from pity and sympathy to disgust and distress. Drawing on some tenets of Erving Goffman’s theory of stigma and Tobin Siebers’ disability aesthetics as critical viewpoints, the paper examines the stigmatisation and repulsion in the form of disgust that individuals with disfigurement encounter and their ability to challenge and overcome these societal constructs.